Newborn Screening for Cystic Fibrosis in Iceland: a Pilot Study - Lizette Cinco Marchadesch 1995- (2023)
Introduction: Cystic fibrosis (CF) is one of the life-shortening autosomal recessive diseases in the Caucasian populations of Europe and North America which is detected and diagnosed through newborn screening (NBS). Prior to starting a NBS program for CF, it is vital to have a fail-safe procedure to minimize risks and maximize benefits. The calculated incidence of cystic fibrosis in Iceland is 1:8,135 based on number of births and CF patients diagnosed clinically from 1955 to 2022. Aim: The objective of this pilot study aims to establish the feasibility of newborn screening for CF in Iceland that will provide a reliable screening process. Methods: Newborn screening for cystic fibrosis was performed by measuring immunoreactive trypsinogen (IRT) with an immunoassay, using the PerkinElmer DELFIA IRT kit. A total of 4,520 stored dried blood spots from the year 2020 were tested and used as a study population. The significance between IRT concentrations and study variables, birthweight, gestational age, age at sampling, length, gender, Apgar score, amino acids, acylcarnitines, and season of child’s birth was conducted with a p-value of 0.05 using IBM SPSS 27.01.1. Results: On the first screening of IRT, 62 samples were above cut-off level (>50 ng/mL). But upon reassaying from the same DBS, 58 samples remained elevated. No newborn was diagnosed with CF in 2020. The elevated IRT concentration could be most likely due to CF carriers or from demographic factors which showed statistically significant association to IRT. Through stepwise logarithmic regression analysis, factors which showed statistically significant to IRT concentration were methionine, season of sampling, C3, Apgar score, birthweight, tyrosine, C14:1, C18:1, C2, and C16:OH. Additionally, all independent variables (significant and nonsignificant) were grouped and analyzed for significance to mean ranks of IRT using Kruskal-Wallis test. The categorized variables which were statistically significant to mean ranks of IRT were the following: gestational age, ...